1997
DOI: 10.1073/pnas.94.1.343
|View full text |Cite
|
Sign up to set email alerts
|

Place cells and place navigation

Abstract: The assumption that hippocampal place cells (PCs) form the neural substrate of cognitive maps can be experimentally tested by comparing the effect of experimental interventions on PC activity and place navigation. Conditions that interfere with place navigation (darkness, cholinergic blockade) but leave PC activity unaffected obviously disrupt spatial memory at a post-PC level. Situations creating a conf lict between egocentric and allocentric orientation (place navigation in the Morris water maze filled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 56 publications
0
71
0
Order By: Relevance
“…However, once in the second chamber, the discharge switched to the direction indicated by a similar card placed in a different reference direction. It also was shown that hippocampal ''place cells'' can both fire in cell-specific reference frame-specific locations (10,11) and can switch between reference frames when the task changes (21) within a complex task (22) and when conflicts between idiothetic and allothetic information appear (23). Despite such changes in stimulus control, these data support the idea that the hippocampus behaves as a coherently organized spatial representation because all of the cells tend to behave in the same way within a recording session.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, once in the second chamber, the discharge switched to the direction indicated by a similar card placed in a different reference direction. It also was shown that hippocampal ''place cells'' can both fire in cell-specific reference frame-specific locations (10,11) and can switch between reference frames when the task changes (21) within a complex task (22) and when conflicts between idiothetic and allothetic information appear (23). Despite such changes in stimulus control, these data support the idea that the hippocampus behaves as a coherently organized spatial representation because all of the cells tend to behave in the same way within a recording session.…”
Section: Discussionmentioning
confidence: 99%
“…This important issue is unresolved in part because it is not certain whether the discharge characteristics of place cells reflect the rat's spatial cognitive state, and to settle this issue, it will take studying the cellular responses during tasks in which momentary spatial cognition can be assessed (10). It already has been shown that place cell discharge is disorganized by arena rotation in the light but not in the dark (8), but this was demonstrated during random searching when the rat was not required to use any particular spatial information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location was considered changed if the displacement exceeded 5% of the distance from the reference location to the most distant point of the arena. The quality of the location-speci¢c ¢ring was expressed by calculating spatial coherence, concentration and dispersion (Muller & Kubie 1989;Bures et al 1997).…”
Section: (D) Analysis Of Pc Activitymentioning
confidence: 99%
“…For the understanding of functions of the HF, it is important to investigate the actual role of place cells in spatial navigation (Bures et al, 1997a(Bures et al, , 1997bZinyuk et al, 2000;Lenck-Santini et al, 2001). A purpose of the present study is to elucidate relationships between activity of HF neurons and goal-directed behaviors acquired dur-ing learning of a novel place task.…”
mentioning
confidence: 99%